Problematizando a relação existente entre o programa Escola Viva e o ensino do esporte competitivo tendo como foco a dimensão atitudinal - Col, Rodrigo Silva Dal (2019)
This work presents the history of the publisher Malha Fina Cartonera, created through an extension project of the University of São Paulo (USP), and also addresses the emergence of the cartonero editorial movement, which is based on the production of books with cardboard covers. The cardboard, which would probably be thrown in the trash, is transformed into colorful covers, gaining relevance and importance in the production of printed books at a lower cost. Based on a field research in the publishing house, located within the USP, interviews and bibliographic investigations, the study shows how the cartoneras are an example of resistance so that the circulation of literature does not depend only on large publishers. In an increasingly competitive and challenging publishing market for writers, finding more accessible ways to publish texts encourages new writers and brings the community closer to books. Some poems published by Malha Fina will be appreciated in this work. As far as theory is concerned, and as cartonerism emerged and most of it is concentrated in Latin America, the concept of Ethos Barroco, by Bolivar Echeverria (1995), is used to affirm this resistance to the capitalist and editorial system, based also on Jacques Rancière's (2005) notes on rationality in the aesthetic regime